Forensic Experts’ Perspectives on Australian Indigenous Sexual Offenders and Factors Important in Evaluating the Risk of Recidivism - Allan, Alfred (International journal of offender therapy and comparative criminology, 2021)
Law and ethics require that risk assessment should be cross-culturally valid and fair, but Australian research in this regard is underdeveloped. A logical first step in progressing the work required to build a strong evidence base on culturally sensitive risk assessment in Australia is to determine the expert views of those in the field. We interviewed 13 Australian evaluators who assess Indigenous sexual offenders’ recidivism risk to determine their perceptions of the risk assessment instruments they use and the attributes they believe evaluators doing cross-cultural assessments should have. Our central findings are that evaluators use the available instruments because they believe that the same factors predict sexual recidivism for Indigenous and non-Indigenous offenders, but that they do so cautiously knowing the limitations of the instruments. Evaluators nevertheless want more research data to guide them when they use the available instruments to assess people from cultures that differ from those of people in the normative sample. Participants acknowledge that the unique challenges of assessing Indigenous sexual offenders require non-Indigenous evaluators to be culturally competent and confident. These findings should be valuable to evaluators and those who train or supervise evaluators and/or intend to establish or improve the validity of risk instruments in Australia.